2017
DOI: 10.1016/j.foodchem.2016.07.104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation studies of persimmon plant ( Diospyros kaki ) for physiological benefits and bioaccessibility of antioxidants by in vitro simulated gastrointestinal digestion

Abstract: III.5. EVALUATION STUDIES OF PERSIMMON PLANT (DIOSPYROS KAKI) FOR PHYSIOLOGICAL BENEFITS AND BIOACCESSIBILITY OF ANTIOXIDANTS BY IN VITRO SIMULATED GASTROINTESTINAL DIGESTIONMartínez-Las Heras, R., Pinazo, A., Heredia, A., Andrés, A. Food Chemistry 214: 478-485 (2017) ABSTRACTThis study aims to analyze the antioxidant benefits from persimmon leaf tea, fruit and fibres taking into account their changes along gastrointestinal digestion. The evolution of polyphenols, flavonoids and antioxidant capacity was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 32 publications
4
44
0
2
Order By: Relevance
“…Our results compared favorably with previous studies on Diospyros kaki L. (Chen et al, 2008;Ercisli et al, 2008;Heras et al, 2017;Oksuz et al, 2015;Pu et al, 2013), and showed similar antioxidant activity. Chen et al (2008) reported that the antioxidant Each value represents the mean of three independent experiments (±SD) Grygorieva, O., Kucharska, A.…”
Section: Antioxidant Activity Of Diospyros Virginianasupporting
confidence: 90%
“…Our results compared favorably with previous studies on Diospyros kaki L. (Chen et al, 2008;Ercisli et al, 2008;Heras et al, 2017;Oksuz et al, 2015;Pu et al, 2013), and showed similar antioxidant activity. Chen et al (2008) reported that the antioxidant Each value represents the mean of three independent experiments (±SD) Grygorieva, O., Kucharska, A.…”
Section: Antioxidant Activity Of Diospyros Virginianasupporting
confidence: 90%
“…Our results compared favorably with previous studies on Diospyros kaki L. (Chen et al, 2008;Ercisli et al, 2008;Heras et al, 2017;Oksuz et al, 2015;Pu et al, 2013), and showed similar antioxidant activity. Chen et al (2008) reported that the antioxidant Each value represents the mean of three independent experiments (±SD) .…”
Section: Thus Dpphsupporting
confidence: 87%
“…For example, in the seeds of white grapes, the decrease in the value of the TPC was almost three times compared to the undigested seeds, and the trend was more or less similar in the pomace faction [17]. A clear decrease in TPC after gastrointestinal digestion was also observed in extracts of pomegranate [18], papaya, jackfruit [19], and in fresh persimmons [20]. However, there are some studies in which there are no clear differences between the TPC of the undigested and digested samples [16,21].…”
Section: Total Phenolic Compounds and Antioxidant Activitymentioning
confidence: 85%